The Influence of Foreign Ownership and Leverage on Firm Value with Financial Distress as an Intervening Variable - B. Andini Nugrahaning Wdhi; Enny Susilowati Mardjono (International Journal of Business and Management Technology in Society, 2024)
Purpose – This research aims to analyse the effect of foreign ownership and leverage on firm value, with financial distress as an intervening variable, specifically in multinational food and beverage companies listed on the Indonesia Stock Exchange. Methodology – This research employs a quantitative approach using multiple regression analysis and path analysis. Data from 2018 to 2022 were analyzed, focusing on foreign ownership, leverage (measured by Debt-to-Equity Ratio), financial distress (using financial ratios), and firm value (measured by Price to Book Value). Findings – Financial distress can be used as an intervening variable between foreign ownership and firm value, where financial distress affects foreign ownership and financial distress also affects firm value. Financial distress cannot be used as an intervening factor between leverage and firm value, where financial distress affects firm value, but financial distress does not affect the leverage variable. Research limitations – This research is limited by its five-year observation period and focuses only on financial ratios within the multinational food and beverage sector in Indonesia. Future research could expand by including different sectors, longer timeframes, and a broader range of financial indicators. Practical implications – This research provides practical insights for investors and corporate managers, especially in multinational firms, regarding the importance of foreign ownership structures and financial health in enhancing firm value.